Evaluating the Impact of Emerging Technologies on Student Learning Outcomes: A Case Study of Kabul University, Afghanistan - Hakimi, Abdurrahman; Turan, Mohammad Nawab; Fazil, Abdul Wajid (PT. Riset Press International, 2024)
This study investigates the integration of emerging technologies in teaching practices at Kabul University, focusing on faculty perceptions, utilization patterns, and associated challenges. Employing a mixed-methods approach, data was collected through surveys and semi-structured interviews from 127 Students across various academic faculties. Quantitative analyses, including ANOVA, regression, and correlation analyses, were conducted to examine relationships between familiarity with emerging technologies, perceived impact on student engagement, and frequency of integration into teaching practices. Thematic analysis of interview transcripts provided qualitative insights into faculty experiences and perspectives. Findings reveal diverse utilization patterns, with a significant proportion of instructors frequently integrating emerging technologies into their teaching practices. However, challenges such as the lack of technical support and infrastructure emerged as significant barriers to technology integration. The study underscores the critical role of faculty training and professional development programs in effectively leveraging emerging technologies to enhance teaching and learning experiences. Recommendations include the implementation of robust support systems and targeted training initiatives to address barriers and maximize the potential of emerging technologies in higher education contexts.